Pengaruh Konseling Motivational Interviewing terhadap Kepatuhan Minum Obat pada Pasien Tuberkulosis Paru di RSUD Batang - Tuti Alawiyah; Menik Kustriyani; Niken Sukesi (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2026)
Compliance with taking medication is very important for pulmonary tuberculosis patients because it can ensure that the tuberculosis infection is controlled and does not spread to other people. Motivational interviewing counseling can help tuberculosis patients increase medication adherence with an empathetic and supportive approach to providing information. Through this technique, counselors can foster the patient's internal motivation to overcome obstacles that arise related to taking medication regularly. This research has gone through an ethical process with No. 000.9/002/KEPKRSUDBTG/1/2025. This type of research is quantitative, a quasi-experimental method with a one group pretest-posttest without control design. The sampling technique in this research used purposive sampling of 30 respondents. Data analysis used univariate and bivariate analysis with the Wilcoxon rank test. The research results show: The patient's level of compliance with taking TB medication before Motivational Interviewing counseling is in the medium category and the low category. The level of patient compliance in taking TB medication after Motivational Interviewing counseling has increased, namely the high category and the medium category. There is an influence of motivational interviewing counseling on medication adherence in pulmonary tuberculosis patients at Batang Regional Hospital. There is a significant difference between the results of compliance with taking TB medication before and after counseling motivational interviewing at Batang Regional Hospital.